2018
DOI: 10.1523/jneurosci.1908-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Disinhibits aCaenorhabditis elegansSensory Neuron by Suppressing Ca2+-Dependent Negative Feedback

Abstract: Neuromodulators, such as serotonin (5-HT), alter neuronal excitability and synaptic strengths, and define different behavioral states. Neuromodulator-dependent changes in neuronal activity patterns are frequently measured using calcium reporters because calcium imaging can easily be performed on intact functioning nervous systems. With only 302 neurons, the nematode provides a relatively simple, yet powerful, system to understand neuromodulation at the level of individual neurons. hermaphrodites are repelled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 73 publications
3
35
0
Order By: Relevance
“…Perhaps it is no surprise that, like in other systems, neural networks employ mechanisms to control their own activity [48][49][50][51] . Such an example can be found in the raphe nuclei, where the serotonin neuron autoregulation properties have been extensively investigated in the hope of identifying viable means of pharmacologically modulating their activity for the treatment of mood disorders 38 .…”
Section: Autoregulation In Neural Systemsmentioning
confidence: 99%
“…Perhaps it is no surprise that, like in other systems, neural networks employ mechanisms to control their own activity [48][49][50][51] . Such an example can be found in the raphe nuclei, where the serotonin neuron autoregulation properties have been extensively investigated in the hope of identifying viable means of pharmacologically modulating their activity for the treatment of mood disorders 38 .…”
Section: Autoregulation In Neural Systemsmentioning
confidence: 99%
“…However, first, we have to consider some caveats. First, there are cases where modulation of calcium transients does not follow modulation of membrane potential [ 32 , 33 ]. Second, the calcium transients in AIY, AIA and AIZ are typically measured in neurites [ 10 12 , 15 , 18 ], and hence could not be detected in brain-wide recordings of nuclear-localized calcium indicators (though, note that one study reported nuclear calcium signals in AIY [ 34 ]).…”
Section: An Updated View Of Sensorimotor Control In C Elegmentioning
confidence: 99%
“…They are thus widely used in neuroscience, yet in many neuron types Ca 2+ imaging does not reflect spiking dynamics, and does not permit to assess high frequency APs or sub-threshold voltage fluctuations 11 . Also, Ca 2+ is an indirect measure of neuronal activity, and neuronal depolarization is not always accompanied by a Ca 2+ increase 12 . Finally, GECIs are less-well suited to detect a hyperpolarization of cells, as there is usually no decrease of Ca 2+ below the basal cytosolic concentration.…”
Section: Introductionmentioning
confidence: 99%